SmartSenti: A Twitter-Based Sentiment Analysis System for the Smart Tourism in Turkey - Salur, Mehmet Umut; Aydin, Ilhan; Alali Alghrsi, Shahed (Ieee, 2019)
Today, it is possible to see smart solutions based on artificial intelligence in almost every area such as smart homes, smart assistants, smart cities, smart campuses as well as smart tourism centers. Smart tourism centers are mainly tourism solutions that targets more visitors. Visitors, before traveling to any tourist center, conduct research on the social media application, and they are generally evaluating previous visitor comments. Considering that there are many social media platforms, evaluating these comments manually requires great effort and time. In this study, we have developed a SmartSenti application that sentiment analysis which was performed on Twitter posts about tourism centers using machine learning and transfer learning methods. We have collected tweets about five touristic place in Turkey. These tweets are classified as positive or negative after pre-processing and feature extracting phase. The classification results are shared visually with the users through the mobile application that we developed.
International Conference on Artificial Intelligence and Data Processing (IDAP) -- SEP 21-22, 2019 -- Inonu Univ, Malatya, TURKEY
Keywords: Sentiment analysis; smart tourism; transductive transfer learning; Twitter; machine learning